Repercussão da segurança alimentar e nutricional sobre o consumo de frutas e hortaliças - Melissa Luciana de Araújo (2016)
The dietary changes that occurred in Brazil in the last decades helped to build and strengthen the food and nutrition security policy. Yet, more knowledge is required about food security-related issues of individuals and households of different population groups and their repercussion on specific food intake, such fruits and vegetables (FV). Objective: To verify the effect of food insecurity on FV intake. Methods: This cross-sectional study included individuals aged 20 years or more enrolled in the Program Academia da Saúde (PAS, Health Gym Program) in Belo Horizonte, Minas Gerais. A pretested questionnaire and the Brazilian Food Insecurity Scale (EBIA) collected socioeconomic, health, and food intake data. The multiple linear regression analysis verified the repercussion of food insecurity on FV intake. Results: A total of 2,817 households of PAS users were assessed. The users had a mean age of 56.9±11.2 years, a median formal education of 7.0 years (4.0-11.0), and most were females (90.6%). Most participants (61.9%) were married or had a partner, and 59.6% of the households were headed by a male. The median education level of the household head was 8.0 years (4.0-11), and the median per capita income was R$ 678.00 (423.75-1,000.00). Most users were not enrolled in welfare programs (95.0%). Some (36.9%) participants were retirees or pensioners, and 29.9% were homemakers. Most households had 1 to 3 dwellers (60.6%), 67.8% did not have dwellers aged less than 18 years, and 55.5% had from one to three individuals aged 60 years or more. The prevalence of excess weight, diabetes, high blood pressure, and dyslipidemia were 63.7%, 16.7%, 53.2%, and 44.3%, respectively. The mean daily FV intake was 374.9 ± 183.7 grams, and more than 70.0% of the sample reported acquiring these items in privately owned produce stores followed by municipal stores/farmers markets (fruits: 35.1% and vegetables: 34.5%) at least once a week (fruits: 58.0% and vegetables: 54.8%). As for the SAN, families with individuals aged less than 18 years 59.0% (n=528) were in food security situation and 41,0% (n=367) were food insecurity, while in other households this value was 73,6 (n=1.414) and 26.4% (n=508), respectively. Adjusted multiple linear regression, adjusted for gender and age showed a negative influence on the situation of food insecurity and FV intake, both in households with individuals aged less 18 years (-51.18; 95%CI: -74.45; -27.91) and among those without individuals aged less 18 years (-61.16; 95%CI: -79.96; -42.37). Conclusion: Food insecurity negatively affected on the fruit and vegetable intake of PAS users. These results show the need to develop actions partnership with the public sector and civil society to correct inequities and promote the intake of healthy foods in order to improve the populations quality of life and health.